LITERATURE REVIEW OF AGRIBUSINESS PRODUCT FINANCING DEVELOPMENT MODEL AT SHARIA BANK - Al Amin, Haris; Siregar, Saparuddin; Sugianto, Sugianto (CV. Radja Publika, 2022)
This study aims to analyze the development model of agribusiness product financing in Islamic banks in Indonesia. The data used in the analysis related to the research topic were taken from journal articles on Google Scholar. Data from these sources were then analyzed using a literature review approach. Based on the results of the analysis, it was found that several models of agribusiness product development at Islamic banks in Indonesia are different from the credit model, this Islamic financing is interest free, profit sharing is based on profit sharing made after the transaction period ends. This paper aims to introduce the Islamic financing model and the prospects for its implementation in the agricultural sector. The results of the study show that Islamic financing is prospective enough to strengthen capital in the agricultural sector. To support its implementation in the agricultural sector, it is necessary to take sides with policy makers as well as intensive socialization of the principles of Islamic financing. The modeling used in this research is a literature study or literature review. The literature study in this research was conducted to study the definition of keywords, to deepen theories and concepts and to identify variables related to the background and context of the research. Study of literature related to the model of developing financing for agribusiness products at Islamic banks in Indonesia, searching for journals using Google Scholar with the keywords